Effective/Differentiating Marketing Strategies of McDonald’s in Malaysia And Indonesia - Dilip D; Rupesh Sinha; Ooi Ler Wei; Daisy Mui Hung Kee; Oh Jia Leei; Pua Ke Shuang; Teoh Jia En; Velia Nofira Permatasari; Liem Gai Sin; Eugene Boadu; Junaid Saifi (Journal of the Community Development in Asia (JCDA), 2021)
McDonald's has become one of the world's most known fast-food companies. The success of McDonald's in growing business makes some individuals genuinely curious as to how McDonald's developed their marketing process and strategy as marketing strategies perform crucial roles for businesses to grow eventually. This case study aims to determine the effective marketing strategies of McDonald in Malaysia compared to with those in other countries such as Indonesia and provide recommendations to deal with the situation McDonald's is faced with. This research, using comparative analysis and focusing on 4P marketing mix components, focuses on the analysis of products, prices, places, and promotions.